WAYS AND MEANS OF DEVELOPING COMMUNICATIVE QUALITIES AND COMMUNICATION SKILLS OF AN EDUCATOR (Academia Science Repository, 2023)
The article talks about ways and means of developing communication skills, developing communication skills and developing them in preschool teachers.